The American Symphony Orchestra A Social History of Musical Taste - Mueller, John H. (Indiana University Press, 1951)
A history of what has been termed the monumental orchestra in America. It traces the growth of the symphony orchestra to its roots in European traditions, recounts the crises which it has overcome, and describes the musical repertoires with which it has regaled its audiences during the past century.